An evolutionary investigation of depressed mood: The relationship between daily stressors and patterns of depressive symptoms. (September 2022) - Maitino, Alissa A.; Rosenfarb, Irwin Ford; Glaser, Dale N.; Keller, Matthew C.
Abstract: Background and objectives: The situation-symptom congruence hypothesis (SSCH; (Keller & Nesse, 2006), grounded in evolutionary theory, argues that different types of adversity should lead to distinct patterns of depressive symptoms that help individuals deal with adaptive challenges. Situation-symptom congruence hypotheses were tested in this study using experience sampling methodology. Methods: Two hundred and sixty-five individuals, including 54% who scored at least 16 on the Center for Epidemiologic Studies Revised Depression Scale, responded to text prompts daily for up to 9 days, reporting depressive symptoms as well as the most stressful event or issue they had experienced or focused on within the past 24 h. Results: Multilevel modeling analyses indicated that the relationships between stressors and depressive symptom patterns were largely consistent with SSCH predictions. All stressors were significantly associated with symptoms hypothesized to be adaptive in response to those stressors. Moreover, in separate analyses, nine of the ten symptoms examined were either predicted by the stressors hypothesized to lead to that symptom or negatively related to stressors hypothesized to not elicit those symptoms. Limitations: It is unclear whether the results generalize to those diagnosed with a major depressive disorder; the study did not assess actual life events. Conclusions: Findings suggest that depressive symptoms may, in part, be adaptations that have evolved through natural selection to help individuals cope with adverse situations. Highlights: Daily stressors were associated with symptoms hypothesized to be adaptive. Symptoms were unrelated to stressors hypothesized to not elicit those symptoms. Depressive symptoms may help individuals cope with adverse situations.